The ability of Anopheles funestus and A. arabiensis to penetrate LLINs and its effect on their mortality [version 3; peer review: 2 approved] - Alex Julius Limwagu; Felician Clement Meza; Letus L Muyaga; Dickson Wilson Lwetoijera (Wellcome Open Research, 2023)
Background: Variation in mosquito body size and the ability to penetrate long-lasting insecticide-treated nets (LLINs) remains unknown. This study evaluated the ability of Anopheles funestus and A. arabiensis to penetrate commercially available treated and untreated bednets and how this behaviour affects mosquito mortality. Methods: Three types of LLINs; DawaPlus 2.0, PermaNet 2.0, Olyset 2.0, and untreated (Safi Net) were tested inside a semi-field system. One hundred 3–5-day-old and non-starved female A. funestus and A. arabiensis were released in a chamber with a sleeping adult volunteer under a treated or untreated bednet. Mosquitoes that penetrated inside the nets were collected every two hours using a mouth aspirator. Live mosquitoes were put in paper cups, fed on glucose ad libitum and their mortality rate was monitored for 48 h. Results: The ability of A. funestus to penetrate treated and untreated bednets was significantly higher than for A. arabiensis for all three LLIN net types (P<0.001). For both species the penetration rate was higher for untreated bednets than treated ones except for the Olyset net. Regardless of the assessed mosquito species, all the mosquitoes that penetrated the net, successfully blood-fed on the sleeping volunteer. Compared to A. arabiensis, significant mortality was recorded for A. funestus that were caught inside Olyset nets within 48 hrs of monitoring (P<0.001). Conclusions: These findings demonstrate the ability of A. funestus and A. arabiensis mosquitoes to penetrate the human-occupied treated and untreated bednets. Despite this ability, mosquitoes that penetrated the bednet succumbed to death within two days.